SYSTEMIC FUNCTIONAL LINGUISTICS ANALYSIS ON LEXICAL METAPHOR USED IN SYLVIA PLATH’S POEMS (ANALISIS LINGUISTIK FUNGSIONAL SISTEMIK PADA PENGGUNAAN METAFORA LEKSIKAL DALAM PUISI-PUISI SYLVIA PLATH) - Faradika, Vicha; Sawirman, Sawirman; Revita, Ike (Universitas PGRI Sumatera Barat, 2019)
This article contains a study of lexical metaphors used in the selected poems of Sylvia Plath entitled “Full Fathom Five”, “The Colossus”, “I am Vertical”, “Ariel”, “Lady Lazarus” and “Edge” which focused on representation of sequence changes of death ideas in the poems. This research is conducted by using systemic functional linguistics theory, especially lexical metaphor by Halliday. It is used to look at the data classification of lexical metaphors. As a qualitative descriptive research, it is assisted by using descriptive statisticin doing the analysis. It aims to find out several important formulas such as mean, modus and percentage from the occurence of lexical metaphor. The result of the analysis shows that there are lexical metaphor with noun-noun concept 50.9%, then the concept of noun-verb 38.6% and noun-adjective 10.5%. The dominance of lexical metaphor occurence with noun-noun concept is the representation of death ideas changes in each poem, including death as unacceptable thing, an unavoidable choice, gate for a rebirth and final solution to all life's problems